2009
DOI: 10.1073/pnas.0807187106
|View full text |Cite
|
Sign up to set email alerts
|

The impact of human-made ecological changes on the genetic architecture of Daphnia species

Abstract: The overenrichment (eutrophication) of aquatic ecosystems with nutrients leading to algal blooms and anoxic conditions has been a persistent and widespread environmental problem. Although there are many studies on the ecological impact of elevated phosphorus (P) levels (e.g., decrease in biodiversity and water quality), little is known about the evolutionary consequences for animal species. We reconstructed the genetic architecture of a Daphnia species complex in 2 European lakes using diapausing eggs that wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
178
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 119 publications
(187 citation statements)
references
References 56 publications
8
178
1
Order By: Relevance
“…As a result, not only is D. galeata able to invade Swiss lakes after they are eutrophied, this taxon is unable to persist after a lake has experienced reoligotrophication, whereas D. longispina survives under both conditions. This pattern provides a mechanistic underpinning for the palaeogenetic patterns observed in several lakes north of the Alps: the appearance of either D. galeata clones or its genes in D. galeata  D. longispina hybrids as primary productivity increased and their subsequent decline following nutrient reduction owing to governmental regulation of wastewater inputs [14,15].…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…As a result, not only is D. galeata able to invade Swiss lakes after they are eutrophied, this taxon is unable to persist after a lake has experienced reoligotrophication, whereas D. longispina survives under both conditions. This pattern provides a mechanistic underpinning for the palaeogenetic patterns observed in several lakes north of the Alps: the appearance of either D. galeata clones or its genes in D. galeata  D. longispina hybrids as primary productivity increased and their subsequent decline following nutrient reduction owing to governmental regulation of wastewater inputs [14,15].…”
Section: Discussionmentioning
confidence: 90%
“…Both species live in Greifensee [14,18], but no clone from Greifensee was used in the experiment to minimize the chance of any local environment by the clone effect. The experiment comprised a full factorial design with two temperatures (168C and 228C) and two food conditions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Diapausing eggs produced by the water flea Daphnia are an exception. Subfossil resting eggs, often viable for up to 100 y and containing sufficient quality DNA for genetic analysis (5), have permitted studies of the effects of eutrophication on genetic structure that are important for the ecology and evolution of freshwater bodies (6). However, there are no equivalent studies in the marine environment, and the effects of environmental changes on intraspecific genetic structure and microevolution of eukaryote protists are poorly understood.…”
mentioning
confidence: 99%
“…Jankowski and Straile (2003) suggested that eutrophication may cause a decreased sexual reproduction in Daphnia species through, for example, changes in the genetic structure of the populations (Brede et al, 2009). In addition, Shurin and Dodson (1997) and Dodson et al (1999aDodson et al ( , 1999b showed that anthropogenic perturbations, such as endocrine disrupter contamination, can inhibit sexual reproduction of Daphnia species.…”
Section: Introductionmentioning
confidence: 99%